Experimental Study of a Ground Vortex: The Effect of the Crossflow Velocity - Barata, Jorge M M (2013)
The study of the complex flowfield produced by a single jet impinging on a wall through a crossflow has been carried out over the past several decades with many different motivations and applications. This type of flow is most relevant to the successful design and operation of vertical and/or short take-off and landing aircrafts. The increased momentum of the wall jet is consistent with the movement of the separation point in the X direction, but the region of higher mean vertical velocity spreads in the wall direction. Nevertheless, their results did not exhibit any bimodal LDV histograms of discrete frequencies that could be associated with any instabilities or oscillations. To avoid the influence of the impinging region, a plane wall jet is produced independently. The wall jet collides with the boundary layer produced using a conventional wind tunnel giving rise to a highly curved region, which can be studied for different velocity ratios between the wall jet and crossflow.